Soil microbial properties after 5 years of consecutive amendment with composted tannery sludge - Ferreira Araujo, Ademir Sergio; Lima Miranda, Ana Roberta; Jacinto Oliveira, Mara Lucia; Santos, Vilma Maria; Pinheiro Leal Nunes, Luis Alfredo; Melo, Wanderley Jose [UNESP] (Springer, 2015)
Composting has been recognised an alternative method to tannery sludge recycling and afterwards to be used in agriculture. As the tannery sludge contains salts and chromium, the application of composted tannery sludge (CTS) should be performed carefully to minimise negative effects on soil microbial properties. Therefore, this study evaluated the effects of 5-year repeated CTS amendment on soil microbial biomass (SMB) and enzyme activities in a tropical soil. CTS was applied during 5 years at 0, 2.5, 5, 10 and 20 Mg ha(-1), and at the fifth year, the microbial biomass C (MBC) and N (MBN), basal and substrate-induced respiration (SIR), metabolic quotient (qCO(2)) and dehydrogenase (DHA) and fluorescein diacetate (FDA) hydrolysis were determined in the soil samples. Soil MBC and MBN showed the highest values with the amendment of 5 Mg ha(-1) CTS. Soil respiration increased with the increase in CTS rates, while SIR showed the highest values with the amendment of 0, 2.5 and 5 Mg ha(-1) CTS. DHA activity showed the highest values with the amendment up to 2.5 Mg ha(-1), while FDA hydrolysis increased up to the rate of 5 Mg ha(-1) CTS. The results show that after 5 years of permanent amendment of CTS, soils amended with 2.5 Mg ha(-1) have SMB and enzymatic activities similar to those in unamended soil.
Keywords: Waste management; Microbial activity; Chromium; Soil quality